DIDACTIC LITERATURE LESSON ON PHILOSOPHICAL NOVEL SOPHIE’S WORLD - Sofiatin Sofiatin (STKIP Muhammadiyah Bogor, 2021)
Literature in written works comes to give aesthetic value and entertainment to the readers. It also has an educational function in purpose to change the way people think. One of which is a novel written by Jostein Gaarder entitled Sophie’s World. Based on didactical value, this novel is categorized as Hybrid literature. Hybrid literature is combined with didactic literature and imaginative literature. Didactically, this novel gives philosophical lessons. Meanwhile imaginatively, it explores readers’ imagination. Sophie’s World was written in simple language and plot that can easily be understood by the readers to learn about philosophy in an easy way. Its progressive plot and its writing style, which tells the story inside the story, make this novel still interesting to read because of its suspension and puzzle on its story. This novel is studied by using a descriptive qualitative method with a content analysis approach, conducted by describing the didactical literature of this novel, analysing the content or didactic expression, and analysing the language use. This novel is highly suggested to be used as learning media for philosophical course taught in Higher Education and as learning media in teaching literature. Besides, the novel Sophie’s World is good to be read by everybody to enrich their philosophical knowledge..